“We will build together”: Sowing the seeds of SEL statewide - Valerie B. Shapiro; Addison M. Duane; Mai Xi Lee; Tiffany M. Jones; Ashley N. Metzger; Sobia Khan; Channa M. Cook; Sophia H.J. Hwang; Brent Malicote; Alejandro Nuñez; Juyeon Lee; Mike McLaughlin; et al. (Social and Emotional Learning: Research, Practice, and Policy)
Social and emotional learning (SEL) has been lauded as important for student success. However, little guidance is available for how educators, scholars, and policymakers can work together to improve SEL implementation in public schools across a state. Here, we describe CalHOPE Student Support – an effort to “sow the seeds” of SEL across California. Invoking the metaphor of a garden, we first discuss the historic developments in California that readied the ground for such work. Then, we lift up the voices of education leaders who have been catalysts for transforming the landscape. Next, we describe our collective vision for a “thriving garden” – the process and outcomes we aim to achieve. We then explain how we harmonized essential elements (e.g., information, support, values, and action) into a comprehensive system for statewide SEL implementation. Then, we share information about our garden’s yield – our successes and ongoing struggles, through the voices of our collaborators. We end with a synthesis of lessons learned (e.g., build capacity for change-making, differentiate support, plan for turnover) for use by other educational leaders seeking to advance SEL in their regions.